Implementation of Strategic Management in Learning to Improve Intisab Pui-Based Life Skills for Students (Case Study at Madrasah Aliyah Daarul Uluum Pui Majalengka) - Rahmatullah, Irfan; Hidayat, Wahyu (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the implementation of strategic management in learning to improve life skills based on Intisab PUI in students at Madrasah Aliyah Daarul Uluum PUI Majalengka. The modern era demands that Islamic educational institutions be able to integrate spiritual values with practical skills, but there is still a gap in the implementation of effective strategies to achieve that balance. Therefore, this study aims to analyze the formulation, implementation, and evaluation of Intisab PUI-based learning strategies, as well as assess its effectiveness in improving students' life skills. The research uses a qualitative approach with a case study method. Data was obtained through in-depth interviews with madrasah heads, teachers, and students, observation of the learning process, and analysis of curriculum documents. The validity of the data is guaranteed through triangulation techniques. The results of the study showed that the formulation of the strategy resulted in the concept of